Intermetalloid and Heterometallic Clusters Combining p‑Block (Semi)Metals with d- or f-Block Metals - Wilson, Robert J; Lichtenberger, Niels; Weinert, Bastian; Dehnen, Stefanie (Chemical reviews, 2019)
Clusters have been the subject of intense investigations since their famous definition launched by Cotton in 1963, and the area has expanded ever since. One obvious development addresses the widening of the definition of what to call a cluster: from purely (transition) metal–metal linked assemblies, as per Cotton’s early denomination, to nonmetal/metal clusters or purely nonmetal cages, like fullerenes, and even noncovalent aggregates such as water clusters. The other extension concerns the broadened spectrum of compositions within the aforementioned cluster types and their corresponding structures that range from trinuclear motifs to clusters with sizes in the range of the hemoglobin unit. This review article reports on one cluster family that has its origins in traditional Zintl anion chemistry but has undergone rapid development in recent years, namely, ligand-free clusters that combine main group and transition metal atoms. Depending on the position of the transition metal atom(s), one refers to such clusters as intermetalloid (endohedral) clusters or as a special type of heterometallic clusters. The predominant synthetic access makes use of soluble Zintl anions. Other pathways for their preparation include traditional solid state reactions of according element combinations or bottom-up syntheses employing low valent organo-main group element sources. This survey will shed light on all of these approaches, with an emphasis on the syntheses that employ soluble Zintl anion compounds. The article will give a comprehensive overview of the currently known compounds, their different synthesis protocols, and analytic techniques for determination of their compositions, structures, and further properties. Additionally, this survey will report peculiarities of bonding situations found within some of the cluster molecules, which were studied by means of sophisticated quantum chemical investigations.